PENYULUHAN PENCEGAHAN PENYAKIT TUBERKULOSIS (TBC) ERA NEW NORMAL - Yanti, Budi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Having good knowledge and attitude related to the prevention of Tuberculosis is very important as control disease efforts and also supported by a positive and appropriate attitude. Actually, positive behavior can improve the prevention of Tuberculosis disease that would support the government to control the disease. This community service aims to improve the knowledge of students about Tuberculosis disease that would inhibit the transmission of disease in the Islamic Boarding School Inshafuddin, Banda Aceh. This community service activity was implemented by presenting counseling information and distributing leaflets about Tuberculosis disease to all students who join in this event. The activity is held on strict health protocols such as open space that meets adequate ventilation requirements and wearing a mask, washing hands first before entering the counseling area, and sitting more than 1 meter apart. The number of students who participated in this event was about 30 students and was attended by several teachers. All activity participants stated that this activity was very useful and could improved knowledge related to Tuberculosis disease.